2010
DOI: 10.1371/journal.pone.0013366
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Face and Object Perception in an Awake Chimpanzee (Pan Troglodytes) Examined by Scalp-Surface Event-Related Potentials

Abstract: BackgroundThe neural system of our closest living relative, the chimpanzee, is a topic of increasing research interest. However, electrophysiological examinations of neural activity during visual processing in awake chimpanzees are currently lacking.Methodology/Principal FindingsIn the present report, skin-surface event-related brain potentials (ERPs) were measured while a fully awake chimpanzee observed photographs of faces and objects in two experiments. In Experiment 1, human faces and stimuli composed of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 51 publications
(79 reference statements)
3
26
2
Order By: Relevance
“…The signals were referenced to the forehead midline (FPz) and a ground electrode was positioned at the left earlobe (Fukushima et al, 2010). The electrodes were filled with Quick GEL and impedances were kept below 6 kΩ.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The signals were referenced to the forehead midline (FPz) and a ground electrode was positioned at the left earlobe (Fukushima et al, 2010). The electrodes were filled with Quick GEL and impedances were kept below 6 kΩ.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, several research groups have reported neural examinations of chimpanzee visual processing (Boysen & Berntson, 1985; Fukushima et al, 2010; Parr et al, 2009). For instance, Parr and colleagues (Parr et al, 2009) conducted a functional neuroimaging study of chimpanzee face processing using positron emission tomography (PET).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decades of research have shown that neural representations of objects and entities exist in monkeys (Sigala et al, 2002), apes (Fukushima et al, 2010) and humans (Kourtzi and Kanwisher, 2001). The abilities of object representation and recognition further apply to social domains such as recognition of faces (Dahl et al, 2007; Dahl et al, 2013), conspecifics (Dahl et al, 2007), and ingroup-outgroup members (Pokorny and de Waal, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…After a long period of step-by-step training, we succeeded in measuring EEG in a fully-awake adult chimpanzee for the first time151617. In the present experiment, we measured ERPs in response to pictures which were a subset of the stimuli used in the chimpanzee memory experiment, in which enhanced memory for affective over neutral pictures was found12.…”
mentioning
confidence: 97%